Improving resilience of the healthcare supply chain in a pandemic: Evidence from Europe during the COVID-19 crisis. Issue 5 (December 2022) - Spieske, Alexander; Gebhardt, Maximilian; Kopyto, Matthias; Birkel, Hendrik
Abstract: The severe scarcity of critical medical supplies caused by the COVID-19 pandemic led to considerable procurement challenges in the healthcare supply chain (HCSC). As ensuring the availability of such supplies during disruptions is critical, the debate on how to increase supply chain resilience in healthcare has gained new momentum. We present empirical evidence from a multi-tier case study spanning nine European medical supplies manufacturers and hospital groups. Based on the resource dependence theory, we investigated procurement-related strategies to improve medical supplies availability. We conducted semi-structured interviews with 39 procurement and supply chain management experts and derived seven propositions on buffering and bridging approaches for managing evolving resource dependencies and thereby strengthening supply chain resilience in a pandemic. Overall, we confirm the resource dependence theory's applicability for explaining companies' mitigation measures in a pandemic disruption. We find that bridging measures within the healthcare supply base, such as offering procurement support for suppliers or leveraging long-term buyer-supplier relationships, are more effective for securing medical supplies than buffering measures. Complementing bridging with buffering, such as extended upstream procurement or resource sharing among hospitals, can lead to superior risk mitigation as capacities of the present supplier base may not suffice. Furthermore, we extend the resource dependence theory by showing that the severity of disruptions caused by a pandemic triggers new forms of buffering external to the HCSC. Both traditional and new buffering measures establish novel flows of medical supplies in the HCSC that can enable higher supply security in a pandemic. Highlights: A healthcare supply chain case study during the COVID-19 pandemic is conducted. Supply chain resilience measures are explored using the resource dependence theory. Bridging is more effective than buffering to improve medical supplies availability. Complementing bridging with buffering leads to better risk management. Severe pandemic disruptions trigger novel, cross-industry buffering measures.